2009
DOI: 10.1111/j.1600-0579.2008.00553.x
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical knowledge in implant dentistry for undergraduate students

Abstract: Implant therapy has evolved into an important part of daily dental practice. Appropriate knowledge of diagnostic and therapeutic options with dental implant therapy is, therefore, mandatory for dental students. The present consensus paper describes the theoretical knowledge as a foundation to the teaching of implant dentistry at the undergraduate level. Students need a solid basic knowledge about biological prerequisites and clinical procedures leading to successful implant treatment and, in particular, an und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 32 publications
0
44
0
1
Order By: Relevance
“…Comparison between studies about undergraduate implant education in 1974 (25) (24) indicate more undergraduate curricula are integrating implant education. The current study also suggests that the volume of teaching is expanding, presumably as a reaction on the demand to educate general dentists to diagnose, provide information and perform basic procedures (7). This process in Europe may also been further facilitated by the developed ADEE guidelines as a result of the first consensus workshop.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Comparison between studies about undergraduate implant education in 1974 (25) (24) indicate more undergraduate curricula are integrating implant education. The current study also suggests that the volume of teaching is expanding, presumably as a reaction on the demand to educate general dentists to diagnose, provide information and perform basic procedures (7). This process in Europe may also been further facilitated by the developed ADEE guidelines as a result of the first consensus workshop.…”
Section: Discussionmentioning
confidence: 95%
“…These programmes have on average 72 ECTS credits, ranging 12 from 180. Respondents reported on average 9.5 students (range [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] in the final year of study. Three of 11 respondents (27%) acknowledged that implant dentistry is a recognised specialty in their country, and 82% of the respondents (9/11) reported that the postgraduate programme has an official university recognition.…”
Section: Independent Implant Dentistry Programmesmentioning
confidence: 99%
See 1 more Smart Citation
“…In cases of periimplantitis, they should have knowledge regarding suitable interventions. 11 The monitoring and maintenance of those implants may fall upon GDPs. 12 Fortunately, a vast majority of the GDPs surveyed thought that they, at least, have a role in educating patients about dental implants and in suggesting the option of dental implants to patients where appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…It is the task of the various dental disciplines to formulate their own specific curriculum for the education of dental students. With regard to the education of undergraduate dental students, in various dental fields European curriculum guidelines have been prepared over the last decade but not for cariology [4,5,6,7,8]. …”
Section: Introductionmentioning
confidence: 99%